2021
DOI: 10.3389/fmed.2021.681549
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Alloimmunization in Sickle Cell Disease? Should We Restore Blood Donation in French Guiana?

Abstract: Patients with sickle cell disease often undergo frequent blood transfusions. This increases their exposure to red blood cell alloantigens of donor units, thus making it more likely that they produce alloantibodies. This cross-sectional study aimed to describe the prevalence of allo-immunization in patients with sickle cell disease who were monitored at Cayenne Hospital in 2016. Of the 451 patients recruited during the study period, 238 (52.8%) were female. There were 262 (58.1%) homozygous sickle cell and 151 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In our cohort, the antibodies identified were mainly of RhCDE and Kell systems, as reported in studies of transfused SCD patients from the United States and Brazil ( 9 ). Different antibodies systems (i.e., MNS and Kidd) and different frequencies of alloimmunization have been recently described in SCD patients in French Guiana when compared to our cohort or those from the United States or Brazil ( 18 ). These might reflect the heterogeneity of donor and recipient populations in different geographical settings, which increases the complexity of data analysis and comparison.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In our cohort, the antibodies identified were mainly of RhCDE and Kell systems, as reported in studies of transfused SCD patients from the United States and Brazil ( 9 ). Different antibodies systems (i.e., MNS and Kidd) and different frequencies of alloimmunization have been recently described in SCD patients in French Guiana when compared to our cohort or those from the United States or Brazil ( 18 ). These might reflect the heterogeneity of donor and recipient populations in different geographical settings, which increases the complexity of data analysis and comparison.…”
Section: Discussionmentioning
confidence: 67%
“…RBCs from Caucasian donors were used. The donor-recipient exact matching for ABO, Rhesus and Kell antigen for RBC compatibility strategy limits alloimmunization, which might further complicate clinical management of patients with SCD ( 9 , 18 , 19 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the optimal timing for DHTR detection remains to be elucidated, current recommendations suggest serologic testing up to 3–4 weeks post‐transfusion may help to identify new alloantibody formation before possible evanescence 9,13,14 . Incorporating hemoglobin studies (either hemoglobin electrophoresis or routine hemoglobin measurement on Complete Blood Count panel) and a four‐week testing window, recent studies performed in other countries found an incidence of 4.2%–4.4% DHTRs per transfusion event in patients with SCD, 15,16 significantly higher than previously believed, with an 11.5% mortality rate in patients with DHTRs 15 . Thus, under‐detection of DHTRs is a significant source of SCD patient morbidity and mortality.…”
Section: Dhtrs Are An Under‐recognized Cause Of Morbidity and Mortali...mentioning
confidence: 99%
“…Patients with SCD require regular blood transfusions, which increase exposure to foreign antigens and elevate the risk of producing alloantibodies that may cause delayed haemolytic transfusion responses and make it difficult to find suitable blood [ 18 , 19 , 20 ]. Moreover, it has been reported that multiple blood transfusions may lead to transfusion-transmitted infections, inflammation, and iron overload [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%